Type 1 Diabetes Mellitus Comorbid with Malnutrition in Siblings - Freidlander Pangestu; Eka Agustia Rini (HM Publisher, 2022)
Background: Diabetes mellitus is a disorder of the metabolic homeostasis controlled by insulin, resulting in abnormalities of carbohydrate and lipid metabolism. Type 1 diabetes mellitus is one of the most common chronic conditions in children. This study aims to describe two cases of type 1 diabetes mellitus accompanied by malnutrition in children at Dr. M. Djamil General Hospital Padang. Case presentation: The case series describes two cases of diabetes mellitus type one with comorbid undernutrition. Both patients had a family history of diabetes mellitus. And their sibling died because of diabetes type 1. Grandmother and grandfather from the father's side had diabetes. The management of this disease consists of the management of type 1 diabetes mellitus and its complications and accompanying malnutrition. Conclusion: The management of type 1 diabetes mellitus includes the administration of insulin according to the monitoring of blood sugar levels and the management of comorbid diseases that accompany it. Education about the use of insulin and diabetes diet patterns is very important for parents and children with type 1 diabetes mellitus.